Examining entry and exit rates of poverty in Turkey: A dynamic probit regression analysis - Bilik, Mustafa (Economic Journal of Emerging Markets, 2023)
Purpose: The purpose of this study is to add to the current poverty dynamics literature by investigating the underlying causes of poverty persistence in Turkey, with an emphasis on both entry and exit rates. Methods: The study analyzes data from the Turkish Statistical Institute's "Survey on Income and Living Conditions" from 2018 to 2021 using dynamic probit models. This large dataset, which gives a detailed picture of socioeconomic situations, helps in properly understanding the complex aspects influencing poverty rates. Findings: The analysis reveals significant poverty persistence in Turkey, influenced by factors such as gender, marital status, employment, and health conditions. According to the research, these variables frequently interact, forming a complex structure that maintains poverty throughout the country. Implications: The findings necessitate targeted interventions to address persistent poverty, considering the diverse influencing factors. This could lead to a reduction in poverty rates and improved socioeconomic conditions for individuals. Originality/Value: This study offers a unique perspective on poverty dynamics in Turkey, focusing on both entry and exit rates. It provides valuable insights for those formulating policies or strategies aimed at poverty reduction, emphasizing the need for a comprehensive approach to poverty alleviation.